Etnogeografie a archeologie údolí Jaghnóbu - Ľubomír Novák (AntropoWebzin, 2014)
The Yaghnob Valley is nowadays considered as (geographically) isolated region; historically the region was not an isolated part of Sogdiana as it was commonly suggested. Archaeological and linguistic data prove that the Yaghnob Valley was inhabited by some ancestors of the Yaghnobis already before the beginning of the Christian era. By the first half of the eighth century AD there are notes suggesting that one of routes connecting Northern and Central Tajikistan led through the Valley. Many archaic features similar to culture and language of ancient Sogdians were kept in the Yaghnob Valley for centuries. Live in the high mountain valley differed from the lifestyle in foothills and steppes of Sogdiana so the ancestors of the Yaghnobis adapted their lives to mountain conditions. Despite its limited ways of communication with surrounding areas the Yaghnob Valley shows an interesting pattern for a study of communication possibilities of ostensibly isolated areas with neighbouring regions.